Altered brain morphology and functional connectivity reflect a vulnerable affective state after cumulative multigenerational stress in rats. (25th August 2016) - McCreary, J. Keiko; Truica, L. Sorina; Friesen, Becky; Yao, Youli; Olson, David M.; Kovalchuk, Igor; Cross, Albert R.; Metz, Gerlinde A.S.
Highlights: Multigenerational stress raised stress vulnerability and emotional state in female rats. Multigenerational stress reduced neuronal density in areas that regulate stress response. Multigenerational stress altered cortical gene expression related to neuroplasticity. Greater stress vulnerability was linked to altered brain activation in manganese-enhanced MRI. Abstract: Prenatal stress is a risk factor for abnormal neuroanatomical, cognitive, behavioral and mental health outcomes with potentially transgenerational consequences. Females in general seem more resilient to the effects of prenatal stress than males. Here, we examined if repeated stress across generations may diminish stress resiliency and cumulatively enhance the susceptibility for adverse health outcomes in females. Pregnant female rats of three successive generations were exposed to stress from gestational days 12–18 to generate multigenerational prenatal stress (MPS) in the maternal lineage. Stress response was measured by plasma corticosterone levels and open-field exploration in each generation. Neuromorphological consequences of MPS were investigated in the F3 generation using in vivo manganese-enhanced magnetic resonance imaging (MEMRI), T2 -relaxometry, and cytoarchitectonics in relation to candidate gene expression involved in brain plasticity and mental health. Each additional generation of prenatal stress incrementally elevated hypothalamic–pituitary–adrenal axis activation, anxiety-like and aversive behaviors in adult female offspring. Elevated stress responses in the MPS F3 generation were accompanied by reduced neural density in prefrontal cortex, hippocampus and whole brain along with altered brain activation patterns in in vivo MEMRI. MPS increased ephrin receptor A5 ( Epha5 ), neuronal growth regulator ( Negr1 ) and synaptosomal-associated protein 25 ( Snap25 ) gene expression and reduced fibroblast growth factor 12 ( Fgf12 ) in prefrontal cortex. These genes regulate neuronal maturation, arborization and synaptic plasticity and may explain altered brain cytoarchitectonics and connectivity. These findings emphasize that recurrent stress across generations may cumulatively increase stress vulnerability and the risk of adverse health outcomes through perinatal programing in females.